2018
DOI: 10.31957/jbp.474
|View full text |Cite
|
Sign up to set email alerts
|

Isolasi dan Identifikasi Bakteri Termofilik dari Sumber Air Panas di Moso Distrik Muara Tami Kota Jayapura Provinsi Papua

Abstract: Thermophilic bacteria are bacteria that are able to survive in environmental conditions with high temperatures. Thermophilic bacteria are one of the important sources of thermostable enzymes that can be isolated from geothermal environments such as hot springs with temperatures ranging from 50–80 oC. Aims of the study to isolate and identify local isolates of thermophilic bacteria from hot springs in Moso Muara Tami District, Papua. The results showed that 7 isolates (A1, A2, A3, A4, B1, B2, and B3) that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Heat-resistant bacteria are commonly isolated from hot springs in various places. These studies continue to be conducted to explore utilization of thermophilic bacteria as producers of protease and kitinase and sone other enzymes (Runtuboi, et. al., 2018;Nuritasari, et.…”
Section: Fig 2 Results Of Analysis Of Exploratory Studies On Bacteria...mentioning
confidence: 99%
See 1 more Smart Citation
“…Heat-resistant bacteria are commonly isolated from hot springs in various places. These studies continue to be conducted to explore utilization of thermophilic bacteria as producers of protease and kitinase and sone other enzymes (Runtuboi, et. al., 2018;Nuritasari, et.…”
Section: Fig 2 Results Of Analysis Of Exploratory Studies On Bacteria...mentioning
confidence: 99%
“…al., (2019) ;Nisa, (2018); Setiawati & Mihardja, (2018) ;Putri, (2013) suggest that phosphate-dissolving bacteria can be isolated from various places such as organic farming soil, ultisol soil, limestone quarry, rhizosphere of coconut tree, tea plant, soybean plant, eruption land, etc. According to Runtuboi, et. al., (2018); Nuritasari, et.…”
Section: Introductionmentioning
confidence: 99%
“…Namun secara keseluruhan, rata-rata bakteri tersebut mampu hidup di suhu yang tinggi atau dapat dikatakan termasuk ke dalam golongan bakteri termofil. Bakteri termofil merupakan bakteri yang mampu tumbuh pada suhu 45-80°C, bahkan ada yang mampu tumbuh hingga 100°C (Rantuboi et al, 2018). Kelompok bakteri seperti ini memiliki kemampuan untuk toleran terhadap suhu lingkungan yang ekstrim serta mampu untuk bertahan hidup dan berkembangbiak pada kondisi tersebut (Ovando-Chacon et al, 2020).…”
Section: Pembahasanunclassified
“…A study conducted in the East Asian region found the presence of the microorganisms such as Legionella spp, Acanthamoeba, Naegleria spp, Microsporidia, Enterovirus, and Human Adenovirus in hot spring water (10)(11)(12)(13)(14). Another study located in the West Asia region identified Acanthamoeba contamination (15,16), while Naegleria spp, Acanthamoeba, and Bacillus spp were found in a study conducted in the Southeast Asia region (4,17). A study in Indonesia revealed that thermophilic bacteria that were successfully isolated from hot springs include Vibrio sp and Bacillus sp (18) guidelines issued by the WHO entitled Guidelines for Safe Recreational Water Environments Volume 2: Swimming Pools and Similar Environments, the various types of microorganisms identified are classified as a danger of microbial infection through ingestion, inhalation, or physical contact (19).…”
Section: Introductionmentioning
confidence: 99%